SKALA KECERDASAN SPIRITUAL REMAJA MUSLIM - Risma Nur Avita; Adhystia Putri H; Milenia Qodariyah; Nawabika Izzah; Achiel Yahya (PSIKOWIPA (Psikologi Wijaya Putra), 2021)
Spiritual intelligence is a combination of two intelligences, including intellectual intelligence and emotional intelligence. In this case, spiritual intelligence is a form of self-adjustment used in guiding individuals to have a meaningful life. According to WHO, what is called an adolescent is an individual who is in the transition stage from childhood to adulthood. When individuals want or are trying to improve spiritually, a deep understanding of Islam is needed, besides that it also improves the implementation of Islamic teachings. The research method on the spiritual intelligence scale of Muslim adolescents that we use is a quantitative research method. The subjects or participants who are targeted in this measuring instrument are Muslim teenagers who have an age range of 12 to 24 years. This measuring instrument has eight experts in the expert judgment stage. Then there are 104 Muslim adolescent respondents who have been willing to fill out and answer items regarding the spiritual intelligence scale. Based on the aspect of spiritual intelligence there are 78 items, then reduced to 26 items that are valid or good and responded well. Based on the alpha[1]cornbach score, it produces a value of 0.856. So it can be concluded that the spiritual intelligence scale of Muslim youth is worthy of being an instrument of measurement.